Self-Focusing of Laser Beams in Analogy of Gravitational Waves - Eser, Aydıroğlu; Mustafa, Halilsoy (Physics Letters A, Elsevier, 1992)
We consider an extended version of Takatsuji’s laser beam — in analogy with null geodesics in the space—time of interacting waves— which focuses itself in a non-linear medium. It is shown that weak“rotational” effects modify the focal points.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/0375-9601(92)91126-C) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Takatsuji’s laser beam; null geodesics; general relativity